Risk factor profile of patients presenting with acute ST-elevation myocardial infraction to a rural hospital in Malaysia - Mohd Shah, Azarisman Shah; Ngow, Harris Abdullah; PA, Melor; Ab Rahman, Jamalludin; A, Fauz; Satwi, Sapari; K., Khairi; S, Noorfaizan; Maskon, Oteh (LIPPINCOTT WILLIAMS & WILKINS, 2008)
Background Cardiovascular disease is one of the most important causes of death in Malaysia and the rate is on the increase. The major contributor to the increasing prevalence of cardiovascular disease is the rise in the risk factor prevalence such as hypertension, diabetes mellitus and hypercholesterolaemia. These modifiable risk factors could be the key in halting this trend. Methods One hundred and thirty three consecutive patients presenting with acute ST elevation myocardial infarction to the coronary care unit of Hospital Tengku Ampuan Afzan, Kuantan, Malaysia were enrolled into a prospective observational study. Results The majority of patients were male 88.7%, presented with anterior or antero-septal myocardial infarct 66.9% with a mean age of 56.4 10.3 years. 72.9% were smokers, 41.3% had hypertension, 30.8% had diabetes and 27.0% had hyperlipidaemia. The mean serum Creatinine 138.1 103.7 mmol/L, fasting blood sugar 7.95 3.98 mmol/L, total cholesterol 5.74 1.40 mmol/L, low-density lipoprotein 3.74 1.22 mmol/L and high-density lipoprotein 1.19 0.63 mmol/L. Conclusion A significant majority of patients were male aged in the mid 50’s, smokers, and presented with acute anterior or anteroseptal myocardial infarction. A significant minority had a history of hypertension, diabetes mellitus or hyperlipidaemia either alone or in combination.